Watak Kepedulian dalam Kepemimpinan Walikota Surabaya, Tri Rismaharini - Yeremias Jena (Jurnal Perkotaan, 2016)
Traditional ethics such as deontology which prioritizing the observance of moral subject to ethical principles, or utilitarianism that weight higher the benefits of the majority rather than the interests of individuals, it is increasingly recognized that such ethical theories have forgotten the relational aspects of moral action. To act morally is in the first place not for the sake of the observance of moral principles, but the recognition that individuals who relate to him is a moral person whose interests must be taken into account, and that the interests of moral patient that gave birth to moral duty is actually the source that drives moral behavior. That is what we labeled as the ethics of care. The author of this paper describes how an ethic of care has colored the leadership characters of Tri Rismaharini, the mayor of Surabaya. The author shows that people‟s interest is the source of moral obligation that drive her to build the city of Surabaya, and that the interests of the people can only be understood in a caring relation with the community itself.